Intersections of Contemporary Art, Anthropology and Art History in South Asia Decoding Visual Worlds - Perera, Sasanka; Pathak, Dev Nath (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Taking South Asia as its focus, this wide-ranging collection probes the general reluctance of the cultural anthropology to engage with contemporary visual art and artists, including painting, sculpture, performance art and installation. Through case studies engaged equally in anthropology and visual studies, contributors examine art and artistic production in India, Sri Lanka, Pakistan, Bangladesh, and Nepal to bring the social and political complexities of artistic practice to the fore. Demonstrating the potential of the visual as a means to understand a society, its values, and its politics, this volume ranges across discourses of anthropology, sociology, biography, memory, art history, and contemporary practices of visual art. Ultimately, Intersections of Contemporary Art, Anthropology and Art History in South Asia simultaneously expands and challenges the disciplinary foci of two fields: it demonstrates to art criticism and art history the necessity of anthropological and sociological methodologies and theories, while at the same time challenging the "iconophobia" of social sciences.